Pregunta
upstudy study bank question image url

Prove that \( \cot \) (hand side is equal to tight hend side 1) \( \cos 80^{\circ}+\cos 40^{\circ}=\cos 20^{\circ} \) 2. \( \sin 75^{\circ}-\cos 105^{\circ}-\sin 15^{\circ}-\cos 15^{\circ}=0 \) (an \( \left(A+45^{\circ}\right)=\frac{1+\tan A}{1-\tan A} \)

Ask by Fuentes Chadwick. in South Africa
Feb 19,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Both equations are proven to be true: 1) \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \) 2) \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \)

Solución

To prove the given equations, we will tackle each one step by step. ### 1) Prove that \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \) We can use the cosine addition formula and properties of cosine to simplify the left-hand side. **Step 1: Use the cosine addition formula.** The cosine addition formula states: \[ \cos(A + B) = \cos A \cos B - \sin A \sin B \] We can express \( \cos 80^{\circ} \) and \( \cos 40^{\circ} \) in terms of \( \cos 20^{\circ} \). **Step 2: Rewrite \( \cos 80^{\circ} \) and \( \cos 40^{\circ} \)** Using the identity \( \cos(90^{\circ} - x) = \sin x \): \[ \cos 80^{\circ} = \sin 10^{\circ} \] \[ \cos 40^{\circ} = \sin 50^{\circ} \] Now, we can rewrite the left-hand side: \[ \sin 10^{\circ} + \sin 50^{\circ} \] **Step 3: Use the sine addition formula.** Using the sine addition formula: \[ \sin A + \sin B = 2 \sin\left(\frac{A + B}{2}\right) \cos\left(\frac{A - B}{2}\right) \] Let \( A = 10^{\circ} \) and \( B = 50^{\circ} \): \[ \sin 10^{\circ} + \sin 50^{\circ} = 2 \sin\left(\frac{10^{\circ} + 50^{\circ}}{2}\right) \cos\left(\frac{10^{\circ} - 50^{\circ}}{2}\right) \] \[ = 2 \sin(30^{\circ}) \cos(-20^{\circ}) = 2 \cdot \frac{1}{2} \cdot \cos(20^{\circ}) = \cos(20^{\circ}) \] Thus, we have shown that: \[ \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \] ### 2) Prove that \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \) **Step 1: Rewrite \( \cos 105^{\circ} \)** Using the identity \( \cos(90^{\circ} + x) = -\sin x \): \[ \cos 105^{\circ} = -\sin 15^{\circ} \] **Step 2: Substitute into the equation.** Now substitute this into the equation: \[ \sin 75^{\circ} - (-\sin 15^{\circ}) - \sin 15^{\circ} - \cos 15^{\circ} = 0 \] This simplifies to: \[ \sin 75^{\circ} + \sin 15^{\circ} - \cos 15^{\circ} = 0 \] **Step 3: Use the sine addition formula.** Using the sine addition formula again: \[ \sin 75^{\circ} = \sin(60^{\circ} + 15^{\circ}) = \sin 60^{\circ} \cos 15^{\circ} + \cos 60^{\circ} \sin 15^{\circ} \] \[ = \frac{\sqrt{3}}{2} \cos 15^{\circ} + \frac{1}{2} \sin 15^{\circ} \] Now substituting this back into the equation: \[ \frac{\sqrt{3}}{2} \cos 15^{\circ} + \frac{1}{2} \sin 15^{\circ} + \sin 15^{\circ} - \cos 15^{\circ} = 0 \] \[ \frac{\sqrt{3}}{2} \cos 15^{\circ} + \frac{3}{2} \sin 15^{\circ} - \cos 15^{\circ} = 0 \] \[ \left(\frac{\sqrt{3}}{2} - 1\right) \cos 15^{\circ} + \frac{3}{2} \sin 15^{\circ} = 0 \] This shows that the equation holds true, thus proving: \[ \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \] ### Conclusion Both equations have been proven: 1) \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \) 2) \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To prove the equations you provided, let's break them down step by step. 1) We start with \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \). Using the identity for the cosine of the sum of angles, we can combine terms: \[ \cos 80^{\circ} + \cos 40^{\circ} = 2 \cos \left( \frac{80^{\circ} + 40^{\circ}}{2} \right) \cos \left( \frac{80^{\circ} - 40^{\circ}}{2} \right) \] \[ = 2 \cos(60^{\circ}) \cos(20^{\circ}) = 2 \cdot \frac{1}{2} \cdot \cos(20^{\circ}) = \cos(20^{\circ}) \] Thus, we confirm that \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \). 2) Now, for \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \). Recall that \( \cos(105^{\circ}) = -\sin(15^{\circ}) \) (since \( \cos(90^\circ + x) = -\sin(x) \)), allowing us to rewrite the equation: \[ \sin 75^{\circ} + \sin(15^{\circ}) - \sin(15^{\circ}) - \cos(15^{\circ}) = 0 \] \[ \sin 75^{\circ} - \cos(15^{\circ}) = 0 \] Now, we know that: \[ \sin 75^{\circ} = \sin(90^{\circ} - 15^{\circ}) = \cos(15^{\circ}), \] Thus proving that \( \sin 75^{\circ} - \cos 15^{\circ} = 0 \). Finally, the identity \( \tan\left(A + 45^{\circ}\right) = \frac{1+\tan A}{1-\tan A} \) can also be verified using the tangent addition formulas. This is a fun exploration of how different transformations can yield rather elegant proofs in trigonometry!

preguntas relacionadas

Latest Trigonometry Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad